G273 Accuracy of Physician Practice as Compared with Pecarn, Catch and Chalice Head Injury Clinical Decision Rules in Children. A Predict Prospective Cohort Study. (24th May 2017) - Lyttle, MD; Borland, M; Phillips, N; Kochar, A; Cheek, JA; Gilhotra, Y; Furyk, J; Neutze, J; Bressan, S; Donath, S; Molesworth, C; Crowe, L; et al.
Abstract : Aims: Clinical decision rules (CDRs) can assist in determining the need for computed tomography (CT) in children with head injuries (HIs). We assessed the accuracy of 3 high quality CDRs (PECARN, CATCH and CHALICE) in a large prospective cohort of head injured children. However in addition to CDR accuracy, the baseline physician accuracy is one of a number of factors which are also important when determining whether a particular rule should be implemented. The objective of this study was to assess the diagnostic accuracy of physician practice in detecting clinically important traumatic brain injuries. Methods: Prospective observational study of children<18 years with HIs of any severity at 10 mainly tertiary Australian/New Zealand centres. We extracted a cohort of children with mild HIs (GCS 13–15, presenting <24 hour) and assessed physician accuracy for the standardised outcome of clinically important traumatic brain injury (ciTBI); we compared this with the diagnostic accuracy of the PECARN, CATCH and CHALICE CDRs. Physician accuracy was calculated based on whether CT was obtained during the initial Emergency Department (ED) visit. Results: Of 20 137 children, 18 913 had a mild HI as defined. Of these 1578 (8.3% = actual CT rate) received a CT scan during the ED visit; 160 (0.8%) had a ciTBI and 24 (0.1%) underwent neurosurgery. Physician practice accuracy for detecting ciTBI based on whether CT was performed had a sensitivity of 157/160 ((98.1% (94.6%–99.6%) and a specificity of 17, 332/18, 753 (92.4% (92.0%–92.8%)). Sensitivity of PECARN <2 years was 42/42 (100.0%, 91.6% to 100.0%), PECARN ≥2 years 117/118 (99.2%; 95.4% to 100.0%), CATCH (high/medium risk) 147/ 160 (91.9%; 86.5% to 95.6%) and CHALICE 148/160 (92.5%; 87.3% to 96.1%). Projected CT rates for PECARN ≤2/≥2 years were 8.0%/9.4% (high risk only) to 41.4%/48.5% (high and intermediate risk factors, considering the unlikely scenario that all patients in the intermediate risk group receive a CT scan), for CATCH 30.2% (medium and high risk) and for CHALICE 22.0%. Conclusions: Physician accuracy was high. The implementation of PECARN, CATCH or CHALICE CDRs in this setting has the potential to increase the CT rate with limited potential to increase the accuracy of detecting ciTBI.